The influence of different current-intensity transcranial alternating current stimulation on the eyes-open and eyes-closed resting-state electroencephalography - Wang, Yao; Hou, Peiyun; Li, Wenjing; Zhang, Mingxing; Zheng, Hongliang; Chen, Xiaogang (Frontiers in Human Neuroscience, 2022)
Transcranial alternating current stimulation (tACS) applies a sinusoidal oscillating current to modulate intrinsic oscillatory activity. Relevant studies of tACS have indicated that tACS can increase spontaneous brain activity in the occipital area. However, few studies have compared the effects of tACS with different current intensities on spontaneous brain activity in the occipital region. In this study, 10-Hz tACS was delivered to the occipital region at different current intensities (i.e., 1 and 2 mA). We investigated the effect of the tACS on both eyes-open and eyes-closed resting-state electroencephalography (EEG). A total of 20 subjects and fifteen subjects were recruited to participate in the 1-mA tACS experiment and the 2-mA tACS experiment, respectively. Ten subjects participated in both experiments. The experimental results demonstrated that both 1-mA tACS and 2-mA tACS could increase occipital resting-state EEG activities. For the eyes-open condition, alpha activity elicited by 2-mA tACS increased significantly greater than that elicited by 1-mA tACS, while 1-mA tACS could produce greater alpha activity compared to 2 mA for the eyes-closed condition. These results suggested that the optimal current intensity might be different for the eyes-open and eyes-closed resting-state conditions, laying a foundation for the subsequent study of occipital tACS on task-state EEG activities.